3D Laser Scanning of Railway Line - Izvoltova, Jana; Pisca, Peter; Kotka, Vladimir; Mancovic, Marian (Communications - Scientific letters of the University of Zilina, 2013)
3D laser scanning is very useful method to reach digital terrain model as the common output of map making. The paper deals with an application of 3D laser scanning in railway track measurements, which belong to the field of engineering surveying. Experimental measurements were carried out on the ballast-less railway construction with the purpose to determine its track geometry by the combination of terrestrial and laser scanning methods. Measurements were carried out in conformity with conditions involved in corresponding technical standards. Surveyors used a variety of firmware, CAD and mathematical software for laser scanning processing to reach the expected outputs in adequate volume, accuracy and reliability.